How to Make You Stay Longer with Me? The Effect of Organizational Climate on Turnover Intention Mediating by Job Satisfaction in Information Technology Company - Gabriella Winda Jovita; Wustari Mangundjaya (Universitas Katolik Soegijapranata, 2019)
Information technology is one of the most sector that continously develop and raise. Irronically, those industry also has the highest turnover rates (13.2%). One of the causes is connected to organizational climate. This study aims to examine the effect of organizational climate on turnover intention by considering job satisfaction as the mediating role in IT (Information Technology) company in Jakarta. Organizational climate is measured by Clior Scale (Zuarez, et.al, 2013) short version with 15 items. Job satisfaction is measured by multidimensional ESI (Employee Satisfaction Index) (Tasios & Giannouli, 2017) with 24 items and turnover intention contains 3 items (Atan, 2016). A quantitative survey was conducted on a non-probability (purposive) sample of 90 employees in IT company in Jakarta. This study uses correlation analysis, multilevel regression and bootstrap to test the direct effect and mediating effect (indirect effect). Correlation test results show that there is a negative correlation between organizational climate and turnover intention, significant correlations also exist between organizational climate and job satisfaction, as well as a negative correlation of job satisfaction and turnover intention. Simple regression analysis indicates that organizational climate is a predictor of job satisfaction, organizational climate and job satisfaction, each of which is a significant predictor of turnover intention. Bootsrapping results show that job satisfaction mediates partially the influence of organizational climate on turnover intention.